Development of an intelligent wireless network for microgrid wind turbines - Li, Kevin GenQuan. (2011)
This project discussed the development of an Intelligent Wireless Sensor Network for Microgrid Wind Turbines. It gives details of the individual modular implementation that constitutes to the development of an Intelligent Wireless Sensor Network. This project will also discuss the motivation of incorporating clean energy into Microgrid.